2004
DOI: 10.1021/cg034212u
|View full text |Cite
|
Sign up to set email alerts
|

Growth Phenomena of Single Crystals of Naphthalene in Supercritical Carbon Dioxide

Abstract: The growth behavior and growth rates of naphthalene single crystals in supercritical carbon dioxide were observed and measured at temperatures 307.7, 312.7, and 317.7 K and pressures 15, 17.5, and 20 MPa to highlight the behavior of crystal growth in the supercritical phase. The morphology of naphthalene crystals did not change during the steady growth in the supercritical phase. The crystal growth rates from the supercritical phase were almost independent of pressure and higher with increasing temperature or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…100 ppm, used as our "baseline" value (Section 5), along with n = 2. Other data in the literature of polycyclic hydrocarbon crystal growth rate kinetics 33 also appear to point to k G (298 K) values in the range of 1 to 100 ppm, with some papers reporting n = 1 (as in the case of naphthalene single crystal growth from supercritical CO 2 solutions near 308−318 K 34 ). We remark that these k G assignments correspond to modest effective incorporation probabilities.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…100 ppm, used as our "baseline" value (Section 5), along with n = 2. Other data in the literature of polycyclic hydrocarbon crystal growth rate kinetics 33 also appear to point to k G (298 K) values in the range of 1 to 100 ppm, with some papers reporting n = 1 (as in the case of naphthalene single crystal growth from supercritical CO 2 solutions near 308−318 K 34 ). We remark that these k G assignments correspond to modest effective incorporation probabilities.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 97%
“…Values of the model parameters k G , n, and Γ repl considered in the present illustrative study are k G = 10 −4 (at T = 298 K; Section 4.2), n = 2, and Γ repl = 10 6 . While the naphthalene/CO 2 crystal growth system has been studied experimentally 34 more-specific growth kinetics data for the phenanthrene−CO 2 system will be needed to refine these preliminary but plausible estimates (also see Section 4.2).…”
Section: Mathematical Model For the Nucleationmentioning
confidence: 99%
“…23,24 Additionally, scCO 2 is nontoxic and can reduce the quantities of organic solvent required for processing. 19,25,26 Supercritical CO 2 has three unique roles that make it suitable for pharmaceutical processing. 20 The first relates to the solvent capacity of scCO 2 , which typically reduces or eliminates the requirement for organic solvents during API production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The properties of supercritical fluids (SCF) have been investigated by many authors with a perspective toward solid-sate control and particle engineering of pharmaceutical compounds. Supercritical CO 2 (scCO 2 ) is the most commonly used SCF due to its low cost and high abundance, as well as its low critical temperature (31.1 °C) and pressure (74.8 bar). , Additionally, scCO 2 is nontoxic and can reduce the quantities of organic solvent required for processing. ,, Supercritical CO 2 has three unique roles that make it suitable for pharmaceutical processing . The first relates to the solvent capacity of scCO 2 , which typically reduces or eliminates the requirement for organic solvents during API production.…”
Section: Introductionmentioning
confidence: 99%
“…Because of obvious disadvantages presented by classical cocrystal production methods, the development of novel and better methods for screening and production of cocrystals is highly desirable. Supercritical carbon dioxide has been used as an alternative media for crystallization reactions, acting either as a solvent or an antisolvent. , Supercritical carbon dioxide (SC-CO 2 ) has been used to induce novel polymorphs, to enable the control of the crystal habit, and has more recently also been described as a novel tool for cocrystal engineering. Padrela et al have shown that indomethacin–saccharin cocrystals could be produced either by supercritical antisolvent or by supercritical atomization as straightforward methods, converting crystal clear solutions into micro- to nanosized particles. Additionally, supercritical atomization has shown potential for the generation of novel cocrystal stoichiometries which had not been produced by classical methods .…”
Section: Introductionmentioning
confidence: 99%